(untitled) (Circe de clásicos y modernos, 2018)
This article analyze ‘birth’ as a political device in Hesiod’work. In the first place, we refer to a political dimension insofar as some births unfold in the framework of power relations, in the setting of the usual tensions inherent in the divine drama in its archetypal account; secondly, we refer to the effects of such births on the topos of the general economy of myth as explanatory logos. This tracing is intended to show that the myth constitutes the real and helps the symbolic configuration of identities and imaginaries.